The Ninth Malaysian Plan and agriculture extension officer competency: a combination for intensification of paddy industry in Malaysia - Mohamed Shaffril, Hayrol Azril; Asmuni, Azizan; Ismail, Azahari (The Journal of International Social Research, 2010)
Agriculture interest in Malaysia has risen. This can be proved through government plans stated in The Ninth Malaysian Plan. One of the agriculture sectors that can be benefited through this plan is paddy industry. It is expected in 2010, the income generated by paddy industry will increase up to 988 million per year, thus depicts the potential it has. Paddy industry in The Ninth Malaysian Plan will be boosted through land rehabilitation and consolidation, increase number on R&D, paddy farmers will be exposed to more agriculture trainings, bigger credit allocation and better drainage and irrigation systems. In order to achieve this, the competency of agriculture extension officer is needed. Based on the previous studies, communication training is indeed important aspects that need to be intensified to strengthen the competency aspect of the agriculture extension officers. Previous studies also has show consistent findings that job performance, attitude, skills, knowledge, quality and quantity of works, use of technology and demography factors play important roles in cultivating competency to agriculture extension officers.